PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG PEMERIKSAAN PAYUDARA SENDIRI PADA SISWI SMK ANALIS KIMIA - jama, fatma; Taqiyah, Yusrah; Alis, Ita S (Universitas Islam Negeri Alauddin Makassar, 2020)
Breast cancer is a breast disorder that is most feared by women. One reason for this disease can not be cured if found at an advanced stage. In fact, if detected early, this disease can actually be treated until healed. One way to detect breast cancer early is by self-awareness. Most women do not do breast self-examination due to lack of knowledge so women who do breast self-examination are still low. This study aims to determine the effect of health education on the knowledge and attitudes of adolescents about breast self-examination on Chemical Analyst Vocational School students. This type of research used in this research is quantitative research with experimental design (quasi-experimental or quasi-experimental) with one group pre-test and post-test designs. The determination of the sample is done by purposive sampling technique with a sample size of 80 respondents. The relationship test was performed using the Wilcoxon Signed Rank Test with the significance level α <0.05. The results of this study indicate that there are differences before and after health education is given a level of knowledge where the value of p = 0,000 is obtained, and the attitudes of adolescents obtained the value of p = 0,000. The conclusion of this study is that health education influences the knowledge and attitudes of adolescents about breast self-examination on Chemical Analyst Vocational School students. Therefore it is very important to be able to detect early symptoms of breast cancer. It is recommended that schools always hold a health outreach to women and work closely with health workers, especially about breast self-examination.